Autophagic stress activates distinct compensatory secretory pathways in neurons - Sierra D. Palumbos; Jacob Popolow; Juliet Goldsmith; Erika L. F. Holzbaur (Proceedings of the National Academy of Sciences, 2025)
Autophagic dysfunction is a hallmark of neurodegenerative disease, leaving neurons vulnerable to the accumulation of damaged organelles and aggregated proteins. However, the late onset of diseases suggests that compensatory quality control mechanisms may be engaged to delay these deleterious effects. Neurons expressing common familial Parkinson’s disease-associated mutations in the leucine-rich repeat kinase 2 (LRRK2) exhibit defective autophagy. Here, we demonstrate that both primary murine neurons and human induced Pluripotent Stem Cells (iPSC)-derived neurons harboring pathogenic LRRK2 upregulate the secretion of extracellular vesicles. We used unbiased proteomics to characterize the secretome of LRRK2 G2019S neurons and found that autophagic cargos including mitochondrial proteins were enriched. Based on these observations, we hypothesize that autophagosomes are rerouted toward secretion when cell-autonomous degradation is compromised to mediate clearance of undegraded cellular waste. Immunoblotting confirmed the release of autophagic cargos and live-cell imaging demonstrated that secretory autophagy is upregulated in LRRK2 G2019S neurons. We also found that LRRK2 G2019S neurons upregulate the release of exosomes containing microRNAs. Live-cell imaging confirmed that this upregulation of exosomal release is dependent on hyperactive LRRK2 activity, while pharmacological experiments indicate that this release staves off apoptosis. Finally, we show that markers of both vesicle populations are upregulated in plasma from mice expressing pathogenic LRRK2. In sum, we find that neurons expressing pathogenic LRRK2 upregulate secretory autophagy and the compensatory release of exosomes to mediate waste disposal and transcellular communication, respectively. We propose that this increased secretion contributes to the maintenance of cellular homeostasis, delaying neurodegenerative disease progression over the short term while potentially contributing to neuroinflammation over the longer term.